2020
DOI: 10.1016/j.cmi.2020.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic investigation of HCV-4d epidemic in Paris MSM HIV population reveals a still active outbreak and a strong link to the Netherlands

Abstract: Objectives: The hepatitis C virus (HCV) epidemic is evolving quickly despite new treatments, and due to behaviour changes increasing at-risk situations. We investigated potential origins and evolution of the HCV-4d French emergence among human immunodeficiency virus (HIV)-infected men who have sex with men (MSM), in Paris in 2003. Methods: We analysed all HCV sequences from the initial Paris outbreak with all newly available sequences publicly available, including sampling date and geographical location, resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
0
10
1
Order By: Relevance
“…For example, in the Netherlands, DAAs became widely available in 2015, and two prospective studies among MSM living with HIV in 2014 and 2016 reported a 51% decrease in HCV incidence between 2014 and 2016 [ 21 ]. Interestingly, a study published in 2020 analysing phylogenetic HCV strains among HIV-infected MSM diagnosed with HCV subtype 4d during the 2003–2007 HCV outbreak highlighted the close links between the French and the Dutch MSM communities [ 22 ]. Additionally, a decreasing trend was observed among MSM living with HIV in the United Kingdom between 2013 and 2018 [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the Netherlands, DAAs became widely available in 2015, and two prospective studies among MSM living with HIV in 2014 and 2016 reported a 51% decrease in HCV incidence between 2014 and 2016 [ 21 ]. Interestingly, a study published in 2020 analysing phylogenetic HCV strains among HIV-infected MSM diagnosed with HCV subtype 4d during the 2003–2007 HCV outbreak highlighted the close links between the French and the Dutch MSM communities [ 22 ]. Additionally, a decreasing trend was observed among MSM living with HIV in the United Kingdom between 2013 and 2018 [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, numerous outbreaks of recently acquired hepatitis C virus infection (RAHC) have been described among people living with HIV (PLWH) worldwide, mainly in HIV‐positive men who have sex with men (MSM) [1–9]. The increased incidence of RAHC in HIV‐positive MSM has been attributed to several factors such as a higher hepatitis C virus (HCV) load in blood and semen [10], sexual practices with an increased risk of mucosal damage, the presence of ulcerative sexually transmitted diseases, a larger number of sexual partners and the use of chem‐sex [11].…”
Section: Introductionmentioning
confidence: 99%
“…25 However, the phylogenetic results of the NS5B region suggested a likely (although inconclusive) association with a France origin, where the genotype 4d has been endemic in the MSM population since about 2000. 2 There are data of extensive dissemination from this origin to neighbor countries 9 and transcontinental. 6 Sexual transmission of HCV in the MSM population with and without HIV infection, even heterosexual transmission as reported in the female HIV-infected patient in this study, is a public health problem nowadays despite the extensive use of DAA.…”
Section: Discussionmentioning
confidence: 99%